PENGETAHUAN LOKAL PEMANEN LEBAH MADU (APIS DORSATA) DI DESA CENRANA BARU, KECAMATAN CENRANA, KABUPATEN MAROS - Fauzan, Ahmad; Dassir, Muhammad; Muin, Andi Fika Faradiba (Jurnal Riset Multidisiplin Agrisosco, 2024)
This study purpose is to analyze the local knowladge from bee forest (Apis dorsata) Harvester in Cenrana Baru Village of Cenrana Subdistrict of Maros District. This research is held in May –August 2023 in Cenrana Baru Village of Cenrana Subdistrict of Maros District. Local knowledge is knowladge that belong to some society or group specific that inherited by hereditary from generation to generation and focused to surroundings, culture dan local tradition. This research use qualitative descriptive methode that describe local knowledge of bee forest harvester in Cenrana Baru Village of Cenrana Subdistrict of Maros District. There are two types of data used in this research, primary data and secondary data. Primary data obtained from observation and interview results from bee forest’s harvester in Cenrana Baru Village of Cenrana Subdistrict of Maros District. While secondary data obtained from literature that related to research, general data of researchlocation and others. The results stated that honey bee harvesting in Cenrana Baru Village is still derived from local knowledge owned by the community. This can be seen from the methods used in the search for beehives, the equipment used in the implementation of harvesting and the harvesting methods carried out. The harvesting process of forest bee honey harvesting in Cenrana Baru Village has values such as economic, socio-cultural and historical that will benefit the community both in Cenrana Baru Village and the general public.